Guatemala : Selected Issues and Analytical Notes. (IMF Staff Country Reports; Country Report ;, 2014)
This Selected Issues note estimates Guatemala's potential output and output gap using the production function approach, univariate statistical filters, and multivariate models based on the Kalman filter method. In the production function approach, potential output is modeled as a function of potential labor and capital inputs, and total factor productivity (TFP). Results are robust to different methodologies and suggest that its potential output growth is about 3.5 percent and the output gap is on average closed. Structural breaks in potential output were identified in 1994, 2003, and 2008, which coincide to the Mexican tequila crisis, the free trade agreement with the US, and the financial crisis. Going forward, it is critical to undertake structural reforms to strengthen capital, labor, and TFP growth in order to accelerate potential growth. Univariate statistical methods provide a simple measure of potential output. The production function approach also indicates that the absence of productivity growth is a significant barrier to potential output growth.